Pelatihan Pembuatan Soal Melalui Penguatan Evaluasi Berbasis Higher Order Thinking Skills dan Asesmen Kompetensi Minimum - Wahidin Wahidin; Ahmad Subhan; Ahmad Husin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2023)
The aim of the community service activities is to train teachers to create questions based on Higher Order Thinking Skills (HOTS) and Minimum Competency Assessment (AKM) in madrasas by explaining the concepts, characteristics, and procedures for creating questions based on HOTS and AKM in madrasas in a comprehensive manner. general. The method of implementing this service uses the training method. The service was carried out at MA Thalabul Irsyad Kuala Kapuas. The participants are MA teachers. Thalabul Irsyad Kuala Kapuas, numbering 20 people. The results of the service show that this service provides upgraded knowledge and information to teachers regarding creating HOTS and AKM-based questions. With this training, teachers know and understand the concept and method of creating Hots and AKM-based questions in general and matters related to Hots and AKM-based evaluations. It is hoped that they will be able to implement them in the assessment process and be able to develop students' interests and talents. In this way, learning will be more optimal.